2004
DOI: 10.1007/s10549-004-9453-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with axillary presentation breast cancer

Abstract: We present our experience of 50 cases of occult primary tumours presenting as axillary metastases, all with histological report of adenocarcinoma compatible with mammary carcinoma. After bilateral US and mammography, with MRI and mammoscintigraphy where necessary, ipsilateral breast cancer was suspected in 23 cases and quadrantectomy performed. Breast cancer was found only in 12 (24%). In the other 27 women there was no clinical or instrumental suspicion of breast cancer or other primary disease site, so the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Several studies have reported that the 5‐year OS of OBC patients ranges from 59.4% to 100% . In the present series, the 10‐year OS of OBC patients was 88.03%.…”
Section: Discussionsupporting
confidence: 42%
“…Several studies have reported that the 5‐year OS of OBC patients ranges from 59.4% to 100% . In the present series, the 10‐year OS of OBC patients was 88.03%.…”
Section: Discussionsupporting
confidence: 42%
“…24,12,1822 Two of those studies produced an improved recurrence-free survival among patients who received RT to the breast compared with patients who underwent observation only. 24 Although the number of patients in these studies was very small, none demonstrated a benefit from mastectomy compared with BCT plus RT.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported single-institution results in this clinical subset with 5-year OS rates that range from 76% to 100% (Table 4). [2][3][4]12,[18][19][20][21][22] Two of those studies produced an improved recurrence-free survival among patients who received RT to the breast compared with patients who underwent observation only. [2][3][4] Although the number of patients in these studies was very small, none demonstrated a benefit from mastectomy compared with BCT plus RT.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of OBC is reported to be 0.3-1.0%, with peak incidence at around 55 years of age [1][2][3]. Due to the low number of patients included in published series, the outcome of OBC is still unclear, though a favourable outcome has been reported in small series of patients [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%